2010
DOI: 10.1007/s12263-010-0194-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, pro-apoptotic, and anti-proliferative effects of a methanolic neem (Azadirachta indica) leaf extract are mediated via modulation of the nuclear factor-κB pathway

Abstract: Azadirachta indica (neem tree) is used in traditional Indian medicine for its pharmacological properties including cancer prevention and treatment. Here, we studied a neem extract's anti-inflammatory potential via the nuclear factor-jB (NF-jB) signaling pathway, linked to cancer, inflammation, and apoptosis. Cultured human leukemia cells were treated with a methanolic neem leaf extract with or without tumor necrosis factor (TNF)-a stimulation. Inhibition of NF-jB activity was demonstrated by luciferase assay a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 63 publications
4
75
0
2
Order By: Relevance
“…Similar studies conducted before showed potent anti-inflammatory activity of methanol and chloroform extract of both plants [26][27][28] . …”
Section: Discussionsupporting
confidence: 77%
“…Similar studies conducted before showed potent anti-inflammatory activity of methanol and chloroform extract of both plants [26][27][28] . …”
Section: Discussionsupporting
confidence: 77%
“…It is well known that NF-κB is constantly functional in the cell as a transcription factor protein [18]. In resting cells, NF-κB and IκB form an inactive cytoplasm complex.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we provided evidence that nature provides excellent inhibitors of NF-jB: we showed that curcumin [21][22][23]; b-lapachone and emodin, sanguinarine, and capsaicin [24]; kawains [25]; naphtopyrones [26]; cardenolides [27,28]; heteronemin [29]; polyketide derivatives [30]; chalcones [31,32]; and neem leaf extract [33] efficiently inhibit NF-jB cell signaling pathways. Recent reports demonstrate that this is a very active field of research worldwide [6,22,[34][35][36][37][38][39].…”
Section: Nuclear Factor Kappa B Cell Signaling Pathwaysmentioning
confidence: 99%